Free-floating e-scooter usage in urban areas: A spatiotemporal analysis. (April 2022) - Foissaud, Nicolas; Gioldasis, Christos; Tamura, Shun; Christoforou, Zoi; Farhi, Nadir
Abstract: The emergence and growing popularity of e-scooters has created the need for researchers, policy-makers and urban planners to better understand user behaviors and travel patterns. In this paper, we examine the spatiotemporal patterns of e-scooter trips in 4 European cities: Paris, Malaga, Bordeaux, and Hamburg. We use a GPS dataset which includes position coordinates crossed with the country of registration of the user's bank card. Results suggest that riding frequencies and vehicle rotation are low and seem to be correlated. Average trip distance shows low variability and is of approximately 4.5 miles, while average trip duration is of 12 min. Tourists are major free-floating e-scooter users, ride during daytime, over longer distances, but at lower speeds. In all cities, the peak hour is observed in the afternoon (between 3 and 5 pm). Downtown, waterfront areas and availability of soft mobility infrastructure attract users. Usage is following relatively predictable patterns, especially when used for commuting. Highlights: Average trip distance is of approx. 4.5 miles and average trip duration is of 12 min. Tourists ride during daytime, over longer distances, but at lower speeds. Locals often use FFES for night and weekend leisure activities. In all 4 EU cities the peak hour is in the afternoon (between 3 and 5 pm). Downtown, waterfront and availability of soft mobility infrastructure attract users.